SECOND OPEN CONFERENCE OF INFORMATION SCIENCE IN CANADA: Experience, Problems, Solutions; Research and Practice by Canadians - CAIS, Canadian Association for Information Science (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF